2015
DOI: 10.1016/j.ecolmodel.2015.06.044
|View full text |Cite
|
Sign up to set email alerts
|

Representation of species mixing in forest growth models. A review and perspective

Abstract: a b s t r a c tMixed-species forests can sometimes fulfil forest functions and services better than monocultures and are therefore receiving growing attention in forest science and practice. The productivity of mixtures and the interactions between species are influenced by the availability of different resources and climatic conditions, all of which change spatially and temporally. Models are a valuable tool for understanding and predicting how these interacting factors will influence the growth and other fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
120
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 170 publications
(133 citation statements)
references
References 153 publications
(116 reference statements)
2
120
0
6
Order By: Relevance
“…A combination of routine forest inventory data and the set of functions implemented in the transparent forecast system can be an important support tool for conservation planning in the frame of conservation forest biodiversity. Growth simulation models for the prediction of future forest development represent a promising tool for sustainable management of forest ecosystems (Pretzsch et al 2015, Simon et al 2014. However, growths models have not yet been fully integrated into the forest management practice (Porté andBartelink 2002, Machar et al 2016) and are rarely used to assess the forest management strategies in conservation areas (Sodtke et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…A combination of routine forest inventory data and the set of functions implemented in the transparent forecast system can be an important support tool for conservation planning in the frame of conservation forest biodiversity. Growth simulation models for the prediction of future forest development represent a promising tool for sustainable management of forest ecosystems (Pretzsch et al 2015, Simon et al 2014. However, growths models have not yet been fully integrated into the forest management practice (Porté andBartelink 2002, Machar et al 2016) and are rarely used to assess the forest management strategies in conservation areas (Sodtke et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Increases in species diversity and heterogeneity of other structural attributes can, e.g., stabilize and raise the productivity (Bielak et al, 2014;Lei et al, 2009;Liang et al, 2007;Jucker et al, 2014;Pretzsch et al, 2013Pretzsch et al, , 2015aRío and Sterba, 2009), stability (Griess and Knoke, 2011;Jactel and Brockerhoff, 2007), reduced sensitivity to drought (Grossiord et al, 2014;Metz et al, 2013), habitat diversity (Tews et al, 2004), plant and animal richness (Brunet et al, 2010;Ishii et al, 2004;Roth, 1976), and the aesthetic value (Schütz, 2002;Stölb, 2005) of forest stands. On the other hand more heterogeneous structures can have a negative effect on some taxa (Paillet et al, 2010), on the wood quality (Pretzsch and Rais, 2016), on the effort of forest inventory, planning, and management (von Gadow, 1998;von Gadow et al, 2002), and on the costs of opening up the stands to harvest the timber (Keegan et al, 1995;Kellogg et al, 1996).…”
Section: Practical and Scientific Relevance Of Structural Heterogeneimentioning
confidence: 99%
“…However, there is often interest in the effects of different climatic conditions and novel combinations of species or management. Validated process-based forest growth models could be used to examine these scenarios [35,36]. A recent review of forest growth models found that many could be used for mixed-species forests but very few have been validated by comparing their predictions of complementarity effects against measured complementarity effects [36].…”
Section: Next Stepsmentioning
confidence: 99%
“…Nevertheless, it is clear that this simple framework cannot simultaneously show all the different spatial or temporal gradients, or different processes, that are typically occurring in a single forest. The prediction of dynamics resulting from several simultaneously occurring processes can be achieved using process-based models that contain many of the processes or structural attributes listed in Table 1 [35,36].…”
Section: A Framework For Predicting Spatial and Temporal Changes In Cmentioning
confidence: 99%